Geographic Information System for Student Distribution Area Mapping - Andi Nurkholis; Mega Desi Diah Ayu (Jurnal Informatika Universitas Pamulang, 2021)
Determining MTs Muhammadiyah Metro school's promotion location is often constrained because it has difficulty digging up information on the student's distribution. One of the reasons schools find it difficult to dig up student distribution information is that there is no digital mapping, so that isn't easy to carry out promotion in the right location. This study aims to develop a geographic information system for students' areas visualizing distribution maps. System development is carried out by applying the prototype method. The results showed that GIS could help schools determine students' distribution based on markers with different colors. The GIS test uses the ISO 25010 software testing quality standard consisting of eight aspects and the black-box method to examine system functionality. ISO 25010 testing obtained a value of 86.75%, which, based on the interpretation criteria range, is very feasible. The black-box test result show that the system can function properly as evidenced by a righteousness rate of 100%.